A novel roller pump for physiological flow. Issue 8 (25th March 2020) - Chong, Albert; Sun, Zhonghua; van de Velde, Lennart; Jansen, Shirley; Versluis, Michel; Reijnen, Michel M. P. J.; Groot Jebbink, Erik
Abstract: Having physiological correct flow waveforms is a key feature for experimental studies of blood flow, especially in the process of developing and testing a new medical device such as stent, mechanical heart valve, or any implantable medical device that involves circulation of blood through the device. It is also a critical part of a perfusion system for cardiopulmonary bypass and extracorporeal membrane oxygenation procedures. This study investigated the feasibility of a novel roller pump for use in experimental flow phantoms. Flow rates of carotid flow profile measured directly with the ultrasonic flow meter matched well with the reference flow rates programmed into the machine with similarity index of 0.97 and measured versus programmed flow rates at specific time‐points of peak systolic velocity (PSV): 0.894 vs 0.880, end systolic velocity (ESV): 0.333 vs 0.319, and peak diastolic velocity (PDV): 0.514 vs 0.520 L/min. Flow rates derived from video analysis of the pump motion for carotid, suprarenal, and infrarenal flows also matched well with references with similarity indices of 0.99, 0.99, and 0.96, respectively. Measured flow rates (mean/standard deviation) at PSV, ESV, and PDV time‐points for carotid: 0.883/0.016 vs 0.880, 0.342/0.007 vs 0.319, and 0.485/0.009 vs 0.520; suprarenal: 3.497/0.014 vs 3.500, 0.004/0.003 vs 0, and 1.656/0.073 vs 1.453; infrarenal: 4.179/0.024 vs 4.250, −1.147/0.015 vs −1.213, and 0.339/0.017 vs 0.391 L/min, respectively. The novel roller pump is suitable for benchtop testing of physiological flow.